The Influence of Mutation, Promotion And Compensation, on Employee Performance Through Job Satisfaction In Cross-Functional Programs at The Ministry Of Finance - Moh. Ali Imron; Budisaptorini, Anasthasia Triwulan; Geraldina, Ira (Neo Journal of economy and social humanities, 2024)
For human resource development, enhancing organizational synergy and collaboration, the Ministry of Finance implements a cross-functional program involving mutation and promotion among Echelon I Units of the Ministry of Finance. The main point of this research is how job satisfaction and performance are affected by this cross-functional program, considering mutation, promotion, and compensation in their new positions. This research focuses on forty supervisory-level employees who are directly engaged in the cross-functional program, spread across various regions in Indonesia. The independent variables in this research are mutation, promotion, and compensation, while the dependent variable is performance, with job satisfaction acting as an intervening variable. The variables were measured using a Likert scale. Subsequently, data were analyzed using PLS 3.0. The research results indicate that mutation does not significantly influences job satisfaction, promotion and compensation, however, have a positive impact on job satisfaction. Job satisfaction, mutation, and compensation collectively affect performance, while promotion does not exert a significant influence on performance. Furthermore, job satisfaction does not mediate the relationship between mutation and performance, but it does mediate the effects of promotion and compensation on performance.